Meaning Frames: The Structure of Problem Frames and Solution Frames. - Haase, Louise Møller; Laursen, Linda Nhu (Design Issues)
In recent years, focus on the designer's ability to frame wicked problems has underlined the important positioning of the designer as a key player in the early phases of innovation. However, further clarification and development of the theory and terminology of framing are needed in order to understand and support the rather complex framing process that the design team engages in during the early phases of innovation. There is a need to understand how design teams move from an overall framing of the wicked problem, in literature termed the "problem frame," to creating a meaningful solution. Through in-depth case studies of the framing processes at five design companies, we learn how designers use the overall problem frame as a stepping-stone to constructing a set of "solution frames" in order to move toward a meaningful solution that integrates different perspectives. Together with the problem frame these sets of additional solution frames constitute an overall framing of the meaningful product—a "meaning frame." This overall meaning frame clarifies and sets the boundaries, the values and goals, and the criteria for evaluation of a proposed solution. As such, the study sheds light on the otherwise hidden reasoning process of framing toward a meaningful solution, rather than framing the problem, which a majority of current literature discusses.